Molecular evolution of the Myb family of transcription factors: Evidence of polyphyletic origin. - Rosinski, J.A.; Atchley, W.R. (Journal of Molecular Evolution, 1998)
The Myb family of proteins is a group of functionally diverse transcriptional activators found in both plants and animals that is characterized by a conserved DNA-binding domain of approximately 50 amino acids. Phylogenetic analyses of amino acid sequences of this family of proteins portray very disparate evolutionary histories in plants and animals. Animal Myb proteins have diverged from a common ancestor, while plants appear related only within the DNA-binding domain. Results imply a pattern of modular evolution of the Myb proteins centering on the possession of a helix-turn-helix motif. Based on this it is suggested that Myb proteins are a polyphyletic group related only by a "Myb-box" DNA-binding motif.